2015
DOI: 10.3109/09638237.2015.1101056
|View full text |Cite
|
Sign up to set email alerts
|

Mental illness stigma and disclosure in college students

Abstract: These findings suggest that some college students may find programs aiding in disclosure useful in assisting them to achieve their desire to be "out" with their mental illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 16 publications
1
41
0
Order By: Relevance
“…This is a noteworthy finding as studies have often sought to determine whether the provision of information relating to psychological diagnoses and their treatments, psycho‐education, is effective in alleviating stigma and promoting help‐seeking, often with inconclusive results. At present, we know that mere education, the provision of information to dispute the stereotypes of mental illness, is insufficient to diminish stigma . Many suggest that it is not solely the education provided about mental illness during psychology study that is most beneficial in this regard, but in addition, the fact that training often provides direct contact with individuals struggling mental health difficulties as well as the entrainment of humanistic orientation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a noteworthy finding as studies have often sought to determine whether the provision of information relating to psychological diagnoses and their treatments, psycho‐education, is effective in alleviating stigma and promoting help‐seeking, often with inconclusive results. At present, we know that mere education, the provision of information to dispute the stereotypes of mental illness, is insufficient to diminish stigma . Many suggest that it is not solely the education provided about mental illness during psychology study that is most beneficial in this regard, but in addition, the fact that training often provides direct contact with individuals struggling mental health difficulties as well as the entrainment of humanistic orientation .…”
Section: Discussionmentioning
confidence: 99%
“…If, following awareness of public stigma, the individual also espouses agreement with the negative stigmatized stereotype and believes that the stereotype applies to him or herself, harm to the self, a reduction in self‐esteem, and efficacy may ensue, which in turn undermines efforts at independence and goal‐directed activity . There is empirical evidence to support the progressive development of self‐stigma . This lends credence to the validity of testing self‐stigma as a potential mediator between public stigma and help‐seeking.…”
Section: Introductionmentioning
confidence: 90%
“…However, previous operationalizations of public stigma ask individual respondents to report on perceived stigma from a generic "most people" originally used in Bruce Link's (1987;Link, Mirotznik, and Cullen 1991) Devaluation-Discrimination scale, with few exceptions (Moses 2010; also see Eisenberg et al 2009 for discussion of this issue). These inconsistencies regarding the level of analysis at which public stigma truly takes place perhaps explain the mixed findings on whether public stigma has a positive, negative, or no association with severity of symptoms, disclosure, self-esteem, and treatment (Corrigan et al 2016;Eisenberg et al 2009;Gollust 2008, 2009;Hunter et al 2017;Sirey et al 2001). …”
Section: Introductionmentioning
confidence: 99%
“…Employees may also receive emotional support from colleagues; a common reason for disclosing (Brohan et al, 2012). It has been shown that a large number of different social, psychosocial and demographic factors affect the decision to disclose (Corrigan et al, 2015b). The GMC (General Medical Council) states that disclosure to managers and occupational health is mandatory if there is a risk that a health professional's illness could pose a risk to patients (General Medical Council, 2013).…”
Section: Introductionmentioning
confidence: 99%